Susceptibility Testing of Bacteria Using Maldi-Tof Mass Spectrometry - Burckhardt, Irene; Zimmermann, Stefan (Frontiers in Microbiology, 2018)
Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) was introduced into the microbiological routine more than ten years ago. Since then is has almost replaced biochemical identification. It is unrivaled in terms of accuracy and cost. From a laboratories perspective it would be an ideal method to replace classic susceptibility testing, that is Kirby-Baur agardiffusion or determination of minimal inhibitory concentrations (MICs). First reports on possible assays for susceptibility testing are more than ten years old. However, the developments during the last five years were substantial. This review focuses with some exceptions on the progress, which was achieved during the last decade.